Plant Growth Regulators: An Overview of WOX Gene Family - Haroon Rasheed; Lin Shi; Chichi Winarsih; Bello Hassan Jakada; Rusong Chai; Haijiao Huang (Plants)
The adaptation of plants to land requires sophisticated biological processes and signaling. Transcription factors (TFs) regulate several cellular and metabolic activities, as well as signaling pathways in plants during stress and growth and development. The WUSCHEL-RELATED HOMEOBOX (WOX) genes are TFs that are part of the homeodomain (HD) family, which is important for the maintenance of apical meristem, stem cell niche, and other cellular processes. The WOX gene family is divided into three clades: ancient, intermediate, and modern (WUS) based on historical evolution linkage. The number of WOX genes in the plant body increases as plants grow more complex and varies in different species. Numerous research studies have discovered that the WOX gene family play a role in the whole plant’s growth and development, such as in the stem, embryo, root, flower, and leaf. This review comprehensively analyzes roles of the WOX gene family across various plant species, highlighting the evolutionary significance and potential biotechnological applications in stress resistance and crop improvement.